The Dynamics Of Good And Evil In Leadership: A Study Of Shakespeareâs Macbeth And Kantâs Religion Within Boundaries Of Mere Reason - Khan, Shahida (Universitas Prasetiya Mulya, 2012)
Understanding the nuances of good and evil in literary representation has been a trend in the neo-academic circle. Within the framework of Leadership Studies, the present paper locates Shakespeareâs Macbeth (1606) central to the understanding of the concepts of good and evil in leading. The first section critically introduces the concepts of good and evil and their place in leading and Kantâs view on good and evil. The second section gives a short summary of the plot of the play Macbeth.Â In the third and fourth section I argue that Macbeth is a potential text for an emphatic understanding of good and evil in leading; I highlight the ethical dimension in leading and leadership. It not only argue that the character of Macbeth can be represented as prototypes of understanding the dynamics of righteous and evil leaders, I also suggest that teaching ethical issues of leadership can be strengthened by an analysis of the character of Macbeth. The last section draws parallels with real-life case bringing out the consequences of unethical.DOI :Â https://doi.org/10.21632/irjbs.5.3.1-16Keywords: ethics, evil, good,leadership, leading.